Improving Total Quality through Evaluation and Manipulation of Critical Success Factors - Shamsodin Nazemi; Amir Hussein Okhravi (بهبود مدیریت, 2013)
In this research, with the aim of critical success factors and a decision team of managers from a manufacturing firm, sixteen factors affecting total quality management were recognized. The standing quality of these factors were then evaluated through analysis of data collected by a designed questionnaire that was given to a sample of 50 managers of the firm. The validity of the questionnaire used to evaluate the current position of the firm was confirmed through face validity. The value of %97.1 that was calculated for Cronbach’s alpha indicated good reliability of the instrument. Friedman statistical test showed that the mean of allocated weight to each of the 16 factors of total quality management are not identical. Furthermore, Kruskal Wallis test indicated that there is significance difference among means of identified factors, so that; vision, reward system, and employees participation received the lowest values among 16 faccors. The result of the study suggests that to have a more effective and efficient system through manipulation of total quality factors, management needs to pay more attention to these weak factors.